Experience-based co-design informed development of a toolbox to help optimise primary care support during transition from children’s hospice care: HOPSCOTCH study protocol - Chapman, Emma; Mitchell, Sarah; Fraser, Lorna Katharine; Wozencroft, Jordanne; Morris, Ben; Peat, George; Charles, Tagore; Elverson, Joanna; Carder, Paul; Tallowin, Katie; Magnusson, Josefine; Ziegler, Lucy (BMJ open, 2025)
IntroductionThe HOPSCOTCH study ‘Helping Optimise Primary Care Support During Transition From Children’s Hospice Care’ aims to develop a toolbox to enable engagement of primary care services in the care of young people with life-limiting conditions (LLC) with a specific focus on the point of transition from children’s hospice services.Methods and analysisIndividual interviews will be held with young people with LLC, their families and healthcare professionals (HCPs). In alignment with Experience Based Co-Design (EBCD) methodology, extracts of film and audio from young people and family interviews will be combined to professionally produce a ‘catalyst film’ highlighting key points and experiences before, during and after the transition from children’s hospice care. Role-specific workshops will be held with young people with LLC, their families and HCPs working in primary care, children’s hospices and adult hospice services. The catalyst film will be used in feedback workshops to prompt prioritisation of key issues to take forward into toolbox development in a shared young people, family and HCP workshop. A documentary analysis of resources currently used to support transition and communication between care settings will support contextual understanding of the transition process. Young people, parents and professionals have shaped and continue to have influence over the study delivery as advisors alongside a multidisciplinary steering committee.The study design has been guided by the UK Medical Research Council complex intervention framework. Intervention development draws on the principles of EBCD and is theoretically driven by the Behaviour Change Wheel.Ethics and disseminationThe study is registered with the UK’s Clinical Study Registry (ISCTRN75964234).Ethical approval was obtained from Wales 3 ethics board on 2 July 2025 (IRAS ID 334486). This study will include ongoing dissemination and knowledge transfer to key audiences (young people, parents, service providers, commissioners) via publications, national bodies, knowledge exchange events, web-based platforms, social media and clinical/academic forums.